Pengaruh Pengetahuan Investasi Dan Motivasi Investasi Terhadap Minat Berinvestasi Di Pasar Modal Pada Mahasiswa Fakultas Ekonomi - Prayoga, Ahmad Danang; Salim, Muhammad Agus; Priyono, Achmad Agus (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to examine the influence of investment knowledge and investment motivation on investment interest in the stock market among economics faculty students. Data were collected through questionnaires distributed to economics faculty students from multiple universities. Linear regression analysis revealed that investment knowledge and investment motivation have a significant positive impact on investment interest in the stock market. Students with better investment knowledge and higher investment motivation tend to exhibit greater interest in investing in the stock market. The findings of this research provide guidance for the development of more effective investment education and training programs among economics faculty students. Keywords: Investment Knowledge, Investment Motivation And Invest In The Capital Market